Carbon Market Opportunities in livestock production, and cocoa and coffee agroforestry systems. An analysis of opportunities in Latin America and the Caribbean - Minoli, Sarah (2023)
It provide an overview of the VCM opportunities in the agriculture sector, specifically in sustainable livestock and agroforestry practices, in LAC to the governments of countries in the region that are or are likely to be hosting VCM projects. The report aims to increase governments’ understanding of and capacity to strategically engage with the VCM in the agriculture sector. The target audiences of this report are government decision-makers, specifically ministries of agriculture and environment and advisors to decision-makers in LAC. The report builds on an initial review of opportunities published in September 2023 and offers a more detailed analysis of carbon market opportunities in the livestock sector, and agroforestry systems. These sectors were selected as they are widespread across all LAC countries and offer significant VCM opportunities. An analysis of VCM opportunities in other crop systems and coastal land systems- may be executed at a later stage.